SCLEROCHOROIDAL CALCIFICATION: Clinical Features, Outcomes, and Relationship With Hypercalcemia and Parathyroid Adenoma in 179 Eyes. Issue 3 (March 2015) - Shields, Carol L.; Hasanreisoglu, Murat; Saktanasate, Jarin; Shields, Patrick W.; Seibel, Ira; Shields, Jerry A.
Abstract : Purpose: To describe the clinical features and long-term ophthalmic and systemic findings in patients with sclerochoroidal calcification (SCC). Methods: Retrospective non-interventional clinical chart review of 179 eyes of 118 patients with SCC to evaluate for the relationship of SCC with systemic calcium metabolic abnormalities. Results: The mean patient age at diagnosis was 69 years. There were 47 (40%) men and 71 (60%) women of Caucasian (n = 116, 98%) and Hispanic (n = 2, 2%) heritage. The condition was unilateral in 57 patients (48%) and bilateral in 61 (52%), with a mean of 1.6 lesions per eye (range, 1–7 lesions per eye). The referring diagnosis was choroidal nevus (n = 23, 20%), melanoma (n = 15, 13%), lymphoma (n = 12, 10%), metastasis (n = 6, 5%), osteoma (n = 4, 3%), SCC (n = 6, 5%), and no diagnosis (n = 51, 43%). Of 277 SCC lesions, the most common location was superotemporal quadrant (n = 191, 69%). The largest lesion per eye demonstrated mean basal diameter of 3.6 mm and thickness of 1.8 mm, with yellow or white color (n = 150 lesions, 84%) and located superiorly (n = 105, 61%) at the retinal vascular arcade or near the equator (n = 161, 94%). The lesion demonstrated overlying focal choroidal atrophy (n = 63, 35%) and retinal pigment epithelium atrophy (n = 88, 49%). There was no case of subretinal fluid, hemorrhage, or choroidal neovascular membrane. At mean 4 years follow up, there was no lesion enlargement, decalcification, or related subretinal fluid/hemorrhage, choroidal neovascularization, or vision loss. Ocular treatment was not necessary in any case. Systemic outcomes revealed hyperparathyroidism (n = 9/33, 27%) with parathyroid adenoma (n = 5/33, 15%), Bartter syndrome (n = 1/53, 2%), or Gitelman syndrome (n = 6/53, 11%). Conclusions: Sclerochoroidal calcification is a stable deposition of calcium in the sclera that, unlike choroidal osteoma, has minimal risk for vision loss. All patients with SCC should be evaluated for underlying systemic calcium disorders, especially parathyroid and renal metabolic conditions. Abstract : Sclerochoroidal calcification is a stable deposition of calcium in the sclera that, unlike choroidal osteoma, has minimal risk for vision loss. All patients with SCC should be evaluated for underlying systemic calcium disorders, especially parathyroid and renal metabolic conditions.